2021
DOI: 10.21203/rs.3.rs-685427/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triptonide Effectively Inhibits Triple-Negative Breast Cancer Metastasis Through Concurrent Degradation Of Twist1 And Notch1 Oncoproteins

Abstract: Background: Triple-negative breast cancer (TNBC) is highly metastatic and lethal. Due to a lack of druggable targets for this disease, there are no effective therapies in the clinic.Methods: We explored the ability of active compounds derived from natural herbs to inhibit TNBC metastasis using the methods of molecular biology, cell biology, protein chemistry, pharmacology, and xenografted mice.Results: Here, we showed that triptonide, a small molecule from the traditional Chinese medicinal herb Tripterygium wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…Target identification studies using mice treated with triptonide, mouse testes lysate and a drug affinity responsive target stability (DARTS) assay, [41] demonstrated that triptonide in mice was acting as a protein-protein interaction inhibitor through binding to junction plakoglobin and disrupting its interactions with the Spermatid Maturation 1 (SPEM1) protein, during spermiogenesis. However, triptonide has also been highlighted as a potential anti-cancer agent, which inhibits several other proteins and pathways, [42][43][44] suggesting that triptonide can bind to multiple protein targets in the host. Triptonide displays chemically reactive and metabolically labile functional groups, including a ketone and a number of epoxides, which are moieties that are typically avoided in drug design, to avoid potential toxicity.…”
Section: Phenotypic Approachesmentioning
confidence: 99%
“…Target identification studies using mice treated with triptonide, mouse testes lysate and a drug affinity responsive target stability (DARTS) assay, [41] demonstrated that triptonide in mice was acting as a protein-protein interaction inhibitor through binding to junction plakoglobin and disrupting its interactions with the Spermatid Maturation 1 (SPEM1) protein, during spermiogenesis. However, triptonide has also been highlighted as a potential anti-cancer agent, which inhibits several other proteins and pathways, [42][43][44] suggesting that triptonide can bind to multiple protein targets in the host. Triptonide displays chemically reactive and metabolically labile functional groups, including a ketone and a number of epoxides, which are moieties that are typically avoided in drug design, to avoid potential toxicity.…”
Section: Phenotypic Approachesmentioning
confidence: 99%